Thomas Moore’s Poetry in the Translations of A. A. Kursinsky and V. Ya. Bryusov - Zhatkin, Dmitry Nikolayevich; Yashina, Tatiana A. (Journal of History Culture and Art Research, 2018)
Objectives: The article provides a detailed, holistic analysis of ten translations of the lyrical works of the Irish poet Thomas Moore, created by A.A. Kursinsky and included into his poetic collection “Poluteny. Lyrical poems published in 1894 and 1895 years”. Peculiarities of the perception of this poetic collection are characterized by V.Ya. Bryusov, who noticed A.A. Kursinsky’s intention to “imitate ruthlessly” to K.D. Balmont, with the adoption of both his “appearance” and “the very sense of his poetry” and proposed his own interpretations of two Thomas Moore’s poems from the list of previously translated by A.A. Kursinsky. Methods: In the methodological aspect, the article is based on the foundations of historical poetics, set forth in the fundamental works of Alexander N. Veselovsky, V.М. Zhirmunsky, the theses of M.M. Bakhtin’s theory about dialogue and “stranger’s word”, the works of the representatives of the Leningrad school of comparative-historical literature, created by M.P. Alekseev. In the process of analysis, sociocultural, comparative-historical, cultural-historical and comparative-typological methods of research are used. Findings: At the time of the appearance of A.A. Kursinsky’s translations from the lyrical poetry of Thomas Moore, the free translating-imitations that freely interpreted the ideological and artistic content of the original were widely known to the public as well as the “realistic” translations that were intended to reproduce as accurately as possible the spirit and form of the Irish original. A.A. Kursinsky found some valuable material for philosophical reflection in the poetry of Moore and skillfully preserved the features of the rhythm and melodies of the original works. Moore’s poetry attracted V.Ya. Bryusov’s attention dew to the interpretations of A.A. Kursinsky. V.Ya. Bryusov offered his vision of the works of the Irish poet, reinterpreted separate thoughts and images in a new way. Novelty: In the framework of the comparative analysis of Thomas Moore’s translations written by A.A. Kursinsky and V.Ya. Bryusov, the authors of the article form representations of Russian translators about the peculiarities of perception of ideas, images, artistic details, which characterize the original texts of the Irish poet-predecessor.